Drive for show: putt for dough?: The value of performance measures for professional golfers on the Sunshine Tour and the relationship with earnings - Heathfield, Cameron Spencer (Rhodes University, Faculty of Commerce, Department of Economics and Economics History)
"Drive for show, putt for dough" . This controversial adage has been a prominent sentiment in the game of golf for decades. Empirical evidence investigating its robustness through determinant of earnings inquiries have identified that the most valuable measure of performance in golf is in fact putting. However, with the ever-perpetuating state of golf equipment and the technologies thereof, the distance debate in golf has thus gained traction. Recent investigations and evidence into the adage had identified a trend-shift with regards to the value associated with distance achievable and putting ability in golf. Therefore questioning the relevance of the adage in the modern form of the game. In conducting a determinant of earnings inquiry through the engagement of engineering "pure" performance measures as empirically identified, this investigation is aimed at recognising a similar trend in a South African perspective, on the Sunshine Tour. Utilising a generalised least square regression methodology, the analysis identifies how the value of the marginal product as-sociated with both player and non-player explanatory measures influence real earnings on the Sun-shine Tour. This determination is observed through the means of a comprehensive scenario analysis, demonstrating the effect of marginal performance differences to the degree of 1% and 5% increase in performance. A trend was therefore identified in which the value of the marginal product, and growth in real earnings associated to driving distance at the 5% level were in fact greater than the that of putting ability. The results further denote the robustness of the adage and the inherent value associated to putting vs. driving distance at the 1% level. The conclusion to this investigation demonstrates the importance of opportunistic positions player's put themselves in within tournaments to encourage earnings accumulation. Identified through balanced return on investments for all performance measures to "drive for dough to putt for dough" .
Keywords: Sports Economic aspects -- South Africa; Golfers -- South Africa; PGA Sunshine Tour (Association); Production functions (Economic theory); Marginal productivity; Performance measurement